Breastfeeding: oral in public health implications (Research, Society and Development, 2020)
The promotion of oral health should be part of a broad concept, from birth to adulthood, transcending the merely technical dental dimension, integrating the oral cavity with other public health practices. Breastfeeding arouses interest in the planning of public health policies and projects and motivates the development of research, aiming at diagnosing the situation, with a view to elaborating interventions to expand breastfeeding practice. However, the relationship between breastfeeding and oral disorders is not as widespread in society. Thus, the understanding of the association between breastfeeding and its oral implications becomes an additional reason to emphasize the orientation of mothers regarding the importance of respecting the period of natural breastfeeding as a means of prevention for the child's oral and integral health. In addition to being essential for the construction of strategies that aim to inform women about the dental benefits of this practice. The aim of this study was to review the main oral implications of inadequate breastfeeding. The importance of suction for child development, non-nutritive sucking habits, malocclusion, tooth decay and bottle use will be addressed. There is no doubt that Public Health, by investing in campaigns to encourage breastfeeding and obtaining mothers' adherence, will not only prevent a series of oral problems, but also reduce costs with the treatment of these diseases / oral health problems. In addition to contributing decisively to the better quality of life of individuals.